System Identification Modelling Based On Modification Of All Terrain Vehicle (ATV) Using Wireless Control System - Mohd Aras, Mohd Shahrieel; Mohd Zambri, Mohd Khairi; Abdul Azis, Fadilah; Ab Rashid, Mohd Zamzuri; Kamarudin, Muhammad Nizam (Universiti Malaysia Pahang, Malaysia, 2015)
-